The effectiveness of Hawley and vacuum-formed retainer usage protocols on the stability of fixed orthodontic treatment results - Gorucu-Coskuner Hande; Atik Ezgi; Taner Tülin (Sciendo, 2021)
Objectives: To compare the effectiveness of Hawley and vacuum-formed retainer (VFR) usage protocols on post-treatment stability.